The Essential Oils from Rhizome Extracts of Acorus Calamus Linn Are Potential Herbal Insecticides against Plutella Xylostella Linn Pests - Febri Odel Nitbani; Luter Kadang; Cristiani D. Q. M Bulin (Journal of Applied Chemical Science, 2012)
The present study was conducted to elucidate the activity of essential oil from rhizome extracts of Acorus Calamus Linn as an herbal insecticide against Plutella xylostella Linn pests. The oil from the Acorus Calamus roots was extracted by a water steam distillation method and found 0.005% content. Antifeedant testing was performed by trial option, while insecticidal activity was carried out by feeding and contacting methods. The results showed that the oil have activity as an herbal insecticidal and as an appetite inhibitor to the Plutella xylostella Linn pests. The maximum resistance index values ​​obtained from eating essential oils at concentrations of 4.0% was equal to 80.815%. The toxicity values of the oils, reported as LC50, ​​ as insecticides by the feeding trial and contacting methods were 1.33% and 1.27%, respectively. Those results conclusively indicated that the essential oils of the Acorus Calamus Linn potentially protect the cabbage leaves from the Plutella xylostella Linn pest attacking.